Design and implementation of 3 Axis Magnetic Field Meter - Chong Wei Keat (Universiti Malaysia Perlis, 2008)
Electromagnetic Field Meter (sometime referred to as an Electromagnetic Field Detector) is a scientific instrument for measuring electromagnetic radiation. The electromagnetic radiation is a physical field produced by electrically charge objects, it is one of the four fundamental forces of the nature (the other are gravitation, the weak interaction, and the strong interaction). The field can be viewed as the combination of an electric field and a magnetic field; these two are often describe as the sources of the field. The purpose of this project is to build an EMF Meter to detect the electromagnetic fields that are generated by power lines, electrical appliances, radio waves and microwaves. These electromagnetic radiation usually measure in mGauss or µTesla unit. This project required both hardware and software skills. For hardware description, the data sheet of EMF sensor, multiplexer, analog to digital converter, liquid crystal display and microcontroller need to study before continue to software design. In this project, the 8051 microcontroller is use. The software skills such as assembly language or C programming are required to program the 8051 microcontroller.